2021
DOI: 10.3390/nano11092210
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of the Genotoxic Potential of Pristine Graphene Platelets

Abstract: (1) Background: Graphene is a two-dimensional atomic structure with a wide range of uses, including for biomedical applications. However, knowledge of its hazards is still limited. This work brings new cytotoxic, cytostatic, genotoxic and immunotoxic data concerning the in vitro exposure of human cell line to two types of graphene platelets (GP). It also contributes to the formation of general conclusions about the health risks of GP exposure. (2) Methods: In vitro exposure of a THP-1 cell line to three concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Notably, a proliferation-inhibiting effect of the GRNP materials was observed in MRC-5 cells using RICC and, thus, cell counts as an endpoint. The decrease in RICC in MRC-5 cells seemed to correlate with GRNP thickness, as P5, P3, P2 and P1 demonstrated the lowest BMD30 values (thickness between 0.6 and 1.2 nm), followed by P6 (1-3 nm), P4 (2-10 nm) and P7 (3 nm), and might indicate direct mechanical interference with the cytoskeleton and the mitotic apparatus of the cells, as discussed previously for induction of micronuclei by two types of pristine graphene nanoplatelets in THP-1 cells [45].…”
Section: Cytotoxicity Screeningsupporting
confidence: 62%
See 1 more Smart Citation
“…Notably, a proliferation-inhibiting effect of the GRNP materials was observed in MRC-5 cells using RICC and, thus, cell counts as an endpoint. The decrease in RICC in MRC-5 cells seemed to correlate with GRNP thickness, as P5, P3, P2 and P1 demonstrated the lowest BMD30 values (thickness between 0.6 and 1.2 nm), followed by P6 (1-3 nm), P4 (2-10 nm) and P7 (3 nm), and might indicate direct mechanical interference with the cytoskeleton and the mitotic apparatus of the cells, as discussed previously for induction of micronuclei by two types of pristine graphene nanoplatelets in THP-1 cells [45].…”
Section: Cytotoxicity Screeningsupporting
confidence: 62%
“…The induction of micronuclei by pristine graphene nanoplates and, thus, of fixed DNA damage was furthermore demonstrated in THP-1 cells, underlining the need to include genotoxicity testing in the screening of pristine graphene nanoplates [45]. The same robust endpoints could be mirrored and validated in the in vivo inhalation testing using cytotoxicity, differential cell count in lung lavage fluid as well as histopathological equivalents.…”
Section: Discussionmentioning
confidence: 91%
“…The WST-1 assay was more sensitive than the alamarBlue™ assay, while direct counting of nuclei using highthroughput image cytometry did not reveal any toxicity of the GP1 nanoplates. The WST-1 assay tetrazolium salt is cleaved to a soluble formazan by a complex cellular mechanism that occurs primarily at the cell surface and was reported to yield false-positive results because of the optical interference between nanomaterials and tetrazolium salts and other suggested modes of interactions [31][32][33]. Resazurin in alamarBlue™ is reduced by enzymes located in cytoplasm and mitochondria, and its reduction may signify an impairment of cellular metabolism without necessarily implicating mitochondrial dysfunction [34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on graphene oxide sheets showed the inhibition of the migration of A549 and HeLa cells by direct reaction with actin [64,65]. However, the possible disruption of cytoskeletal fibres by GPs seems to caused be their mechanical action [66].…”
Section: Discussionmentioning
confidence: 99%